KOMIDA: Making microfinance digital in Indonesia - YEOW, Adrian (Institutional Knowledge at Singapore Management University, 2018)
This case chronicles specific background, challenges, and actions taken by an Indonesian microfinancing institution (MFI) as it was implementing a digital mobile system to replace its current manual processes used in its field office operations. From a high level perspective, it describes the challenges faced by an organization that was attempting to implement a new digital initiative but constrained by its resource-scarce, institutionally, and culturally bound environment. At the same time, it highlights that this digital initiative was a critical part of its overall plan for addressing industry demands, increasing competitive pressures, and internal process issues. The case study thus provides in-depth information of motivations behind such a project and the challenges facing the organization as it manages the project with an external IT vendor.